Recovery of data from perfectly twinned virus crystals revisited. Issue 6 (1st June 2016) - Ginn, Helen Mary; Stuart, David Ian
Abstract : An iterative method of map recovery for perfectly merohedrally twinned crystals in the presence of noncrystallographic symmetry is reimplemented and released and an independent metric of success is provided. Abstract : Perfect merohedral twinning of crystals is not uncommon and complicates structural analysis. An iterative method for the deconvolution of data from perfectly merohedrally twinned crystals in the presence of noncrystallographic symmetry (NCS) has been reimplemented. It is shown that the method recovers the data effectively using test data, and an independent metric of success, based on special classes of reflections that are unaffected by the twin operator, is now provided. The method was applied to a real problem with fivefold NCS and rather poor‐quality diffraction data, and it was found that even in these circumstances the method appears to recover most of the information. The software has been made available in a form that can be applied to other crystal systems.